IFNα and its response proteins, IP-10 and SIGLEC-1, are biomarkers of disease activity in systemic lupus erythematosus. Issue 10 (31st October 2012) - Rose, Thomas; Grützkau, Andreas; Hirseland, Heike; Huscher, Dörte; Dähnrich, Cornelia; Dzionek, Andrzej; Ozimkowski, Tobias; Schlumberger, Wolfgang; Enghard, Philipp; Radbruch, Andreas; Riemekasten, Gabriela; Burmester, Gerd-Rüdiger; et al.
Abstract : Objectives: To evaluate and compare the clinical efficacy of three biomarkers for interferon (IFN) activity (measured directly and indirectly) and six traditional biomarkers in indicating current and prospective disease activity (DA) in systemic lupus erythematosus (SLE). Methods: IFNα (dissociation-enhanced lanthanide fluorescent immunoassay), IFNγ-inducible protein 10 (IP-10) (ELISA) and sialic acid-binding Ig-like lectin 1 (SIGLEC-1) (flow cytometry) were measured in 79 accurately characterised patients with lupus and compared with serum titres of Anti-dsDNA (ELISA and radioimmunoassay), Anti-dsDNA-NcX ELISA, Anti-Nuc ELISA, and complement C3 and C4. DA was evaluated using the British Isles Lupus Assessment Group 2004 Index (BILAG-2004) and a modified SLE Disease Activity Index-2000 (mSLEDAI-2K). In addition, 31 clinically quiescent patients were monitored for flares over the course of 180 days. Results: Increased levels of IFNα, IP-10 and SIGLEC-1 were found in 32%, 50% and 86%, respectively, of 66 patients with active SLE. IFNα (r=0.45; p<0.0001) and SIGLEC-1 (r=0.54; p<0.0001) correlated better with BILAG-2004 than did IP-10 (r=0.38; p=0.0002), Farr assay (r=0.40; p=0.0001), Anti-dsDNA-NcX ELISA (r=0.28; p=0.0061), Anti-dsDNA ELISA (r=0.31; p=0.0025), Anti-Nuc ELISA (r=0.25; p=0.0121), C3 (r=−0.43; p<0.0001) and C4 (r=−0.33; p=0.0013). Predictors of SLE flares were disease duration ≤92 months, mild clinical activity (in contrast with no activity), complement C3≤89 mg/dl and IFNα≥20 pg/ml, while only lymphocyte count and age were independent predictors in multivariate analysis. Conclusions: IFNα, IP-10 and SIGLEC-1 emerged as beneficial biomarkers of DA in patients with SLE. Therefore the implementation of IFN biomarkers in standard lupus diagnostics should be reappraised, especially in view of emerging anti-IFN-directed therapies.